2022
DOI: 10.3390/metabo12050445
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute and Chronic Resistance Exercise on the Skeletal Muscle Metabolome

Abstract: Resistance training promotes metabolic health and stimulates muscle hypertrophy, but the precise routes by which resistance exercise (RE) conveys these health benefits are largely unknown. Aim: To investigate how acute RE affects human skeletal muscle metabolism. Methods: We collected vastus lateralis biopsies from six healthy male untrained volunteers at rest, before the first of 13 RE training sessions, and 45 min after the first and last bouts of RE. Biopsies were analysed using untargeted mass spectrometry… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 81 publications
0
31
0
Order By: Relevance
“…The study by Gehlert, Weinisch, Romisch-Margl, Jaspers, Artati, Adamski, Dyar, Aussieker, Jacko, Bloch, Wackerhage and Kastenmuller [ 21 ] had already analyzed the metabolic response after acute resistance exercise and after an additional period of resistance training. Fourteen young male subjects with moderate resistance training experience participated in this experiment, six of whom provided sufficient muscle samples for metabolomics analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study by Gehlert, Weinisch, Romisch-Margl, Jaspers, Artati, Adamski, Dyar, Aussieker, Jacko, Bloch, Wackerhage and Kastenmuller [ 21 ] had already analyzed the metabolic response after acute resistance exercise and after an additional period of resistance training. Fourteen young male subjects with moderate resistance training experience participated in this experiment, six of whom provided sufficient muscle samples for metabolomics analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison showed that only five of the metabolites that had changed after the acute exercise in the first training session were also changed after the last training session. However, it is important to emphasize that the study by Gehlert, Weinisch, Romisch-Margl, Jaspers, Artati, Adamski, Dyar, Aussieker, Jacko, Bloch, Wackerhage and Kastenmuller [ 21 ] did not analyze the metabolic response during low-load training, but only the response in high-load training (8 to 12 maximum repetitions). Thus, it is not possible to compare low- and high-load exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They observed that levels were risen in endurance, resistance, and sprint exercise, with the latter showing the most pronounced increases during and for up to 1‐h post‐exercise and heavily associated with concurrent increases in plasma lactate levels. Similarly to this, Gehlert et al 85 . investigated the metabolome of the vastus lateralis (a muscle within the quadriceps group) at three‐time points across a four‐week resistance exercise training program (prior to, after the first session and after the last session).…”
Section: Analytical Approaches For Ms‐based Investigations In Ses In ...mentioning
confidence: 99%
“…Measured levels of three selected metabolites across a 4-week resistance exercise program showing changes following acute (N-lactoylvaline), chronic (1-stearoyl-GPE (P-18:0), and acute/chronic (xanthosine) training. Adapted with permission from Gehlert et al85 (Copyright 2022 by the authors, CC-BY). https://creativecommons.org/licenses/by/4.0/.…”
mentioning
confidence: 99%